(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2025)
Legitimacy in the context of Islamic family law refers to the legal status of a child within a family based on Islamic law. Legitimacy determines a child’s lineage, whether born within or outside of the marriage period. The primary distinction between an illegitimate child and a legitimate child lies in the method of determining paternity and the rights afforded to the latter. An illegitimate child cannot be attributed to his father, even if he is the biological parent. Consequently, such a child is not entitled to inheritance, maintenance, or custody from the father, often leaving the child feeling marginalized and inferior. This study examines the rights afforded to illegitimate children and explores the methods of determining paternity while proposing approaches to clarify these rights. Adopting a qualitative methodology, the research involves library research, where materials related to this topic have been critically analysed. The findings identify three main methods for determining paternity and reveal that, regardless of a child’s legitimacy status, they have rights protected under Islamic law, including Malaysia’s Islamic family law. Keywords: Illegitimate child, Islamic law, method, rights, solutions, legitimacy Full Text: PDF